2006
DOI: 10.1002/anie.200602439
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Yeast Cell Cycle with a Photocleavable α‐Factor Analogue

Abstract: The budding yeast Saccharomyces cerevisiae is widely used as a model organism for studying many biological processes and systems, particularly for understanding the cell cycle. The yeast peptide pheromone α-factor (WHWLQLKPGQPMY) activates the mating pathway in MATa cells, arresting the cell cycle in the G1 phase. This arrest is used as a tool for synchronizing yeast cultures and for investigating signaling events involved in the pathway and other processes related to morphogenesis and transcription. Herein we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…44, 5666 While chemically cleavable bifunctional cross-linkers are readily available, the previously described photocleavable cross-linkers have not been commercialized and require significant synthetic efforts. As a starting point, we chose sulfo-SMCC (sulfosuccinimidyl-4-(N-maleimido-methyl)cyclohexane-1-carboxylate), a commercially available, water-soluble, heterobifunctional cross-linker with amine and sulfhydryl reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44, 5666 While chemically cleavable bifunctional cross-linkers are readily available, the previously described photocleavable cross-linkers have not been commercialized and require significant synthetic efforts. As a starting point, we chose sulfo-SMCC (sulfosuccinimidyl-4-(N-maleimido-methyl)cyclohexane-1-carboxylate), a commercially available, water-soluble, heterobifunctional cross-linker with amine and sulfhydryl reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches based on exploiting photocleavable crosslinkers have proven to offer a rapid and efficient route for syntheses of many photocleavable bioconjugates for applications in diagnostics and therapeutics. 44,[56][57][58][59][60][61][62][63][64][65][66] While chemically cleavable bifunctional cross-linkers are readily available, the previously described photocleavable cross-linkers have not been commercialized and require significant synthetic efforts. As a starting point, we chose sulfo-SMCC (sulfosuccinimidyl-4-(N-maleimidomethyl)cyclohexane-1-carboxylate), a commercially available, water-soluble, heterobifunctional cross-linker with amine and sulfhydryl reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4) Several caged peptides and proteins, which undergo UV-responsive main chain cleavage to alter their bioactivities, were developed to clarify mechanisms of action of original uncaged peptides/ proteins. [5][6][7][8] These caged peptides/proteins contain a UVresponsive artificial amino acid such as 2-nitrophenylglycine; therefore laborious de novo design and synthesis of a new amino acid will be required if the peptides/proteins should re-spondtoastimulusotherthanUV.Inthiscontext,westarted to invent a stimulus-responsive peptide-bond-cleaving residue (Spr), which can respond to various stimuli by just replacing its protecting group 2) ( Fig. 1A).…”
Section: Stimulus-responsive Amino Acidmentioning
confidence: 99%
“…Photoactivatable enzymes and enzyme substrates are well-established tools for the investigation of biological function and catalytic mechanism (15)(16)(17)(18)(19)(20). Using a photocleavable yeast peptide pheromone (a-factor, WHWLQLKPGQPMY), Parker et al (21) recently demonstrated that the arrest of MATa cells at the G1 stage of division is possible with brief exposure to light. Such control allows for synchronizing yeast cell cultures and investigating signaling processes related to morphogenesis and transcription.…”
mentioning
confidence: 99%